EFFECT OF CONTEXTUAL-BASED LEARNING (CBL)ON STUDENTS' CONCEPT COMPREHENSION AND SCIENTIFIC ATTITUDES IN LEARNING PLANTS TRANSPORT SYSTEM - Maulani, Dineu (2014)
Skripsi ini melaporkan tentang pengaruh contextual-based learning (CBL) terhadap pemahaman konsep dan sikap scientific siswa di salah satu sekolah Sekolah Internasional di Bandung dalam pembelajaran sistem transport pada tumbuhan. Konteks digunakan untuk mengatasi banyak masalah dalam belajar IPA, terutama dalam belajar sistem transport pada tumbuhan dalam mata pelajaran biologi. Penelitian ini menggunakan metode quasi-experiment dengan desain pretest dan posttest. Data didapat dari kelas eksperimen (N=11) dan kelas kontrol (N=11). Pemahaman konsep siswa diukur berdasarkan Bloom'staksonomi (revisi) pada level kognitif tertentu melalui tes objektif dan dianalisis menggunakan SPSS 22.0 untuk windows. Sedangkan sikap scientific diukur dengan menggunakan Likert-scale dengan beberapa indikator, seperti: objectivity, curiosity, questioning, and justifying conclusions with evidence (Munby 1983 in Jin & Ming, 2002). Hasil penelitian menunjukkan bahwa siswa yang belajar dengan menggunakan contextual-based learning memiliki pemahaman konsep dan sikap scientific yang lebih baik dibandingkan dengan kelas kontrol yang menggunakan demonstrasi. Ini terjadi karenasiswa yang belajar melalui contextual-based learning mengalami hands-onactivity yang memberi dampak positif terhadap motivasi dan sikap scientific siswa. This paper reports the effect of contextual-based learning (CBL)on concept comprehension and scientific attitudes of students at one of International School in Bandung in learning plant transport system. Contexts are used to eliminate many problems in learning science, particularly in learning plant transport system topic in biology subject. This research uses quasi-experiment method with pretest and posttest design. Data are collected from experiment class (N=11) and control class (N=11). The concept comprehension of students are measured based on Bloom's taxonomy cognitive level through objective test and being analysed by using SPSS 22.0 version for windows. On the other hand, scientific attitudes were measured by using Likert-scale with some indicators,such as:objectivity, curiosity, questioning, and justifying conclusions with evidence (Munby 1983 in Jin &Ming, 2002). The result shows that the students who learn through contextual-based learning have better concept comprehension and scientific attitudes than another class which uses demonstration. This occurs because the students who learn through contextual-based learning experience hands-on activity which has positive influence on students motivation and scientific attitudes in learning science.